FACTOR ANALYSIS OF STRESS LEVELS AMONG PARENTS OF CHILDREN WITH DISABILITIES - Ade Irma Nahdliyyah; Martani, Rahajeng Win; Nur Baiti Nasution; Septiana Arifadhi; Endang Axtia (Nursing Sciences Journal, 2025)
Parenting stress among parents raising children with disabilities is a mental health concern that significantly impacts caregiving quality and family well-being. This study was conducted to identify factors associated with parenting stress levels among parents of children with disabilities in the Pekalongan Residency. The purpose of this study was to analyze the relationship between parental characteristics, social support, illness uncertainty, and the type of child’s disability with parenting stress. This research employed a descriptive analytic design with a cross-sectional approach and involved 39 parents as respondents. Data were collected using validated questionnaires and analyzed using the chi-square test. The results showed that the majority of parents experienced a moderate level of parenting stress (61.5%). There were significant associations between parenting stress and several factors, including the parent's gender, level of social support, illness uncertainty, and the type of the child’s disability (p<0.05). These findings highlight the importance of implementing family-based interventions and strengthening social support to reduce parenting stress among parents caring for children with disabilities.